Agent-based Negotiation Solution for Enterprise Business Collaboration - Cretan, A.; Coutinho, C.; Bratu, B.; Jardim-Goncalves, R. (15th China-Europe International Symposium on Software Engineering Education, 2019)
This paper addresses the issues of Enterprise Business Collaboration by proposing a distributive software framework to support the coordination of multiple simultaneous negotiations that may take place in a dynamic networked environment. Within a competitive environment, each enterprise wants to retain its decision-making autonomy and to disclose as little business information as possible. In this context, this paper proposes to develop a software business framework for the management of simultaneous multi-agent negotiations among competing enterprises. An industrial application scenario is described for validating and verifying the proposed solution.